ОСОБЕННОСТИ ТЕРАПИИ ТРЕВОЖНЫХ РАССТРОЙСТВ У БОЛЬНЫХ В УСЛОВИЯХ КОМОРБИДНОСТИ - А. М. Шутов; Е. В. Ефремова; А. А. Страхов (SINAPS LLC, 2015)
Comorbidity degrades the quality of life, leads to social exclusion, increased mortality The aim of this study was to investigate the efficacy and tolerability of the drug Afobazol in comorbidity patients of therapeutic profile. 19 patients of therapeutic profile with anxiety disorders (5 males and 14 females, mean age was 49,4 ± 16,3 years) were studied during 6 weeks. Comorbidity, efficacy and tolerability of Afobazol were estimated. All patients completed the course. Effective average daily dose was 50 mg (30 to 60 mg/day). There were a reduction of anxiety disorders, improvement the quality of life and cognitive function after treatment of Afobazol There was acceptable compliance to treatment of Afobazol. Afobazole was well- tolerated by patients.tolerability Afobazol comorbid patients.